Effects of single-session perturbation-based balance training with progressive intensities on resilience and dynamic gait stability in healthy older adults - Zhu, Ringo Tang-Long; Schulte, Friederike A.; Singh, Navrag B.; Ma, Christina Zong-Hao; Easthope, Chris Awai; Ravi, Deepak K. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSingle-session perturbation-based balance training (PBT) has demonstrated improvements in dynamic stability during the initial step following perturbation in older adults. However, its broader effects on comprehensive balance recovery remain inconclusive. This pilot laboratory-based randomized controlled study investigated the impact of personalized single-session PBT on reactive balance control during walking, employing advanced stability analysis techniques.MethodsTen participants in the training group (67.1 ± 2.8 years; 5 males & 5 females) underwent a single session consisting of 32 unpredictable treadmill-induced slips and trips of progressively increasing intensity, while ten participants in the control group (72.8 ± 5.2 years; 5 males & 5 females) engaged in unperturbed treadmill walking. Key outcome measures included margin of stability (MoS) parameters: minimum MoS and the number of recovery steps, and resilience parameters: peak instability and recovery time, assessed at baseline, immediately post-intervention, and 3 months post-intervention following an unexpected treadmill slip.ResultsIn the training group, participants exhibited significant increases in minimum MoS values immediately post-intervention (−33 ± 84 mm; p < 0.001) and 3 months post-intervention (−71 ± 70 mm; p < 0.01) as compared to pre-intervention (−140 ± 87 mm); they also showed a significant reduction in peak instability immediately post-intervention (34 ± 14 mm; p = 0.019) as compared to pre-intervention (57 ± 25 mm). These changes were not observed in the control group. However, neither group demonstrated significant alterations in the number of recovery steps or recovery time across the different assessment periods.Discussion and conclusionIn conclusion, single-session PBT enhanced reactive balance control by improving the magnitude of post-perturbation responses, but it did not significantly influence the speed of recovery to baseline conditions.